Perfect storm [large type] - Shelton, Paige (Shelton, Paige. Alaska wild series, 2025)
"Beth Rivers needs to disappear. Her one-time kidnapper, Travis, is on his way to her town in Alaska, and she's losing time to get out quickly. The perfect spot for Beth and her boyfriend, Tex, to hide presents itself in a camp in the woods, away from Benedict. But when their trip takes them by Blue Mine, a small community that has seen tragedy over the last couple months, plans get diverted. Beth and Tex bring the widow of a recently murdered man back to Benedict for Police Chief Gril to investigate, only to find that nothing is quite what it seems. When the woman vanishes, Beth must be on high alert for further danger. Who knows what other unwelcome disappearances or appearances might be lurking in the unforgiving Alaska storms."--